Система для тестирования параметров технологического оборудования - Белей, Р. С. (My University, 2020)
The aim of the work is to select the elements and construct a combination of components for the control module of the device for testing the parameters of the technical devices. The main functions are: – measure the temperature of the object with the help of an integral digital sensor; – control of the heater located in the layout; – transfer of measured data to a PC using a serial interface; – receiving control commands from the PC using a serial interface. The control module of the device for testing the parameters of the technical devices collects information about the state of the object with the help of sensors (temperature, pressure, humidity) through the input module.
Keywords: технологическое оборудование; тестирование технологического оборудования; эксплуатация технологического оборудования; BigData